Analisis Peningkatan Kinerja Pegawai Melalui Pengembangan Karier Dan Disiplin Kerja Yang Di Dukung dengan Pemberian Motivasi Pada PT. J. A. Wattie Kendal - Mukhlidin, Mukhlidin; Rowiyani, Rowiyani; Muslikhun, Alfin (STIE AMKOP, 2024)
This study aims to analyze how employee performance is influenced by career development variables and discipline with motivation as the mediating variable at PT J.A. Wattie Kendal. This study has a population of 126 people and all samples were taken using the census method. The method of analysis used in this research is path analysis. The results of data testing show Hypothesis 1 (H1) that good career development can increase employee motivation. Hypothesis 2 (H2) results in high level of work discipline that will affect employee motivation for the better. Hypothesis 3 (H3) states that providing good motivation can improve employee performance. Hypothesis 4 (H4) states that good career development can influence employee performance. While Hypothesis 5 (H50) states that a high level of work discipline will also improve employee performance. The results of testing hypothesis 6 (H6) states that good motivation is able to mediate career development which results in good employee performance. While testing hypothesis 7 (H7) states that good work motivation is able to bridge work discipline with employee performance. So it can be said that work motivation is able to be a good mediator for career development variables and work discipline on employee performance in PT. J.A Wattie Kendal. Keywords: Career Development, Discipline, Motivation, Employee Performance